2017
DOI: 10.3390/s17061319
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network-Based Early-Age Concrete Strength Monitoring Using Dynamic Response Signals

Abstract: Concrete is one of the most common materials used to construct a variety of civil infrastructures. However, since concrete might be susceptible to brittle fracture, it is essential to confirm the strength of concrete at the early-age stage of the curing process to prevent unexpected collapse. To address this issue, this study proposes a novel method to estimate the early-age strength of concrete, by integrating an artificial neural network algorithm with a dynamic response measurement of the concrete material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The authors conclude by stating that the approach proposed in the work has the potential to be applied to in situ hydration monitoring of reinforced concrete structures. More research in the field of concrete strength prediction can be found in recent studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Investigations On the Emi Techniquementioning
confidence: 99%
“…The authors conclude by stating that the approach proposed in the work has the potential to be applied to in situ hydration monitoring of reinforced concrete structures. More research in the field of concrete strength prediction can be found in recent studies [ 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Investigations On the Emi Techniquementioning
confidence: 99%
“…www.mdpi.com/journal/sensors associated damage index based on wavelet-packet analysis was developed to help interpret the data. The development of smart-aggregate technology accelerated research on piezoceramic transducers in concrete structures in many applications, such as hydration monitoring [49][50][51], impact detection [52][53][54][55], blast-damage monitoring [56], bond-slip or debonding detection [57][58][59], and concrete compactness monitoring [60,61].…”
Section: Piezoceramic Transducersmentioning
confidence: 99%
“…In another study, Castro et al investigated the feasibility of using low-cost piezoelectric sensors to identify partial discharges in the mineral insulating oil of power transformers [ 18 ]. In a recent study, Kim and Park [ 19 ] proposed a novel method for estimation of the early age strength of concrete by introducing an artificial neural network algorithm to process the dynamic response measurements of concrete structures. They used both electromechanical impedances and guided ultrasonic waves signals, which were obtained from an embedded piezoelectric sensor module.…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on Neural Networks (NN) have been widely proposed in the context of SHM applications [ 19 , 26 , 27 , 28 ]. Recently, new classes of artificial networks, such as Probabilistic Neural Network (PNN) and Fuzzy ARTMAP Network (FAN), have been proposed based on their considerable performances, such as improved accuracy rates and reduced time consumption.…”
Section: Introductionmentioning
confidence: 99%